A Case Study of Using Numerical Analysis to Assess the Slope Stability of National Freeways in Northern Taiwan - Hao-Wei Chiu; Yi-Hao Tsai; Chao-Wei Tang; Chih-Yu Chu; Shong-Loong Chen (Applied Sciences)
Taiwan is located at a junction of tectonic plates, which results in frequent earthquakes. Its terrain is mostly hilly, and its rainfall ranks among the highest in the world. Each of these elements affects the stability of slopes in various regions of Taiwan. Several slopes along Taiwan’s Freeway 1 and 5 have experienced landslides and rockfalls. It is imperative that the slope stability of these national freeways be analyzed to avoid future slope collapses brought on by precipitation or other outside factors. Thus, three sites on Taiwan’s Freeway 1 and 5 were chosen for numerical slope stability analysis in this study. PLAXIS 2D CE (Version: 24.02.00.1144) finite element software was used in this study to simulate and analyze the safety of freeway slope protection projects. Displacements induced by normal and high groundwater levels were discussed. Moreover, a pseudo-static study of slope displacements under seismic conditions was performed. According to the results of the numerical study, the force operating on the slope was centered on the sliding surface when the groundwater level was normal, and it extended to the top when the groundwater level was high. By comparison, under seismic conditions, the force acting on the slope extended to the whole slope. Furthermore, the slope safety factor of Site 1 was greater than the design specification value in three different scenarios. This confirms that the slope protection project at Site 1 is effective.